Comparison of Bond Strength in the Different Class of Resin Cements to Cast and CAD/CAM Co-Cr Alloys. (26th December 2021) - Sadighpour, Leyla; Mostafavi, Azam S.; Pirmoradian, Maryam; Alipuryalda, Fatemeh
Abstract : Objectives . Despite the widespread use of resin cements in cementing dental restorations, their bond strength to CAD/CAM base metal alloys is not widely studied. This study aimed to evaluate the microshear bond strength ( μ SBS) between cobalt-chrome (Co-Cr) alloys fabricated using casting or CAD/CAM methods with three types of resin cements. Materials and Methods . Fifty Co-Cr blocks were prepared with CAD/CAM or casting technique. Specimens were divided using primer or not and bonded to three types of resin cements: Panavia F2, RelyX Unicem, and Duo-Link. The differences between the mean μ SBS values were analyzed using the two-way ANOVA test and Tukey analysis ( α = 0.05). The mode of failure was evaluated using a stereomicroscope. In addition, the specimens were examined by scanning electron microscopy (SEM) based on two received signals: backscattered electrons (SEB) and secondary electrons (SEs). One intact alloy specimen in each group was analyzed by energy-dispersive X-ray spectroscopy (EDX). Results . Most of the specimens in the no-primer group were prematurely debonded. Statistical analyses showed that the interaction between the alloy substrate and cement type was significant (p = 0.001 ). The bond strength of Panavia F2 was significantly higher than Duo-Link in the CAD/CAM group (p = 0.001 ). SEM evaluation confirmed the difference in grain structures, while EDX showed no remarkable difference in the chemical composition of the alloy substrates. Conclusion . Alloy fabrication technique may influence the bond strength of resin cements. In the CAD/CAM group, cement containing MDP molecules exhibited higher strength than the etch-and-rinse one.